Ecogroups and maternal haplogroups reveal the ancestral origin of native Chinese goat populations based on the variation of mtDNA D‐loop sequences - Wenjuan Qin; Daosong Chen; Panpan Guo; Lixing Hu; Xiaodong Zheng; Jin Cheng; Hongquan Chen (Ecology and Evolution, 2023)
Abstract China is rich in goat breeding resources. Officially recognized local goat breeds are mainly distributed in agro‐ecological regions. The population structure and matrilineal origin of native Chinese goats can be used to formulate protection and utilization strategies for these genetic resources. In this study, the genetic structure and maternal origin of native Chinese goats were investigated using mtDNA D‐loop sequences. A total of 329 goat samples from 25 Chinese indigenous goat populations and five introduced goat breeds from abroad were collected; these populations were distributed in four ecogroups designated as Southwest, South‐central, the North China Plain, and Foreign‐ecogroup. A larger average number of nucleotide differences and richer nucleotide diversity were observed in South‐central and Foreign‐ecogroup, whereas these were lower in Southwest. The 216 haplotypes divided into several haplogroups, of which HapA contained 99 haplotypes distributed in Southwest, the North China Plain, and Foreign‐ecogroup with high frequency (0.53–0.77), whereas the frequency of HapA in South‐central was <0.09. HapB was mostly found in South‐central (0.5538) and was distributed to the North China Plain (0.2667), while it was rare in Southwest (<0.08) and Foreign‐ecogroup (<0.07). According to the estimation of kinship and ancestry, HapA had five ancestors (A2, A3, A5, A10, and A12), HapB had a single maternal ancestor (A8), and HapC had two maternal ancestors (A1 and A4). This study showed that native Chinese goat breeds were mainly divided into three haplogroups (HapA, HapB, and HapC) and goat populations have expanded in the ecological regions.